Operative outcomes after laparoscopic splenectomy with special reference to prophylactic antibiotics. Issue 4 (8th November 2018) - Matsuda, Tsunemi; Kubo, Shoji; Ueno, Masaki; Takifuji, Katsunari; Yamaue, Hiroki; Takemura, Shigekazu; Tanaka, Shogo; Shinkawa, Hiroji; Yamada, Koichi; Kakeya, Hiroshi
Abstract: Introduction: We conducted a retrospective study to investigate the progress of the operative outcome after laparoscopic splenectomy (LS), with a special reference to the administration of prophylactic antibiotics (PA). Methods: The study included 123 patients who underwent elective LS. Operative outcomes before and after the operative procedure was standardized and the impact of treatment with PA on surgical‐site infection were investigated. Results: With regard to complications, wound infection developed in one (0.8%), portal trunk thrombosis in one (0.8%), pancreatic fistula in one (0.8%), postoperative bleeding in two (1.6%), pleural effusion in one (0.8%), and reoperation because of bowel injury in one (0.8%). Although morbidity did not differ between patients in the early (until the end of 2010) and late (after the beginning of 2011) periods, intraoperative blood loss was lower in patients in the late period. During the late period, no patients required conversion to open surgery. The proportion of patients with surgical‐site infection did not differ between those who received PA 1 h before the start of surgery and every 3 h during surgery and those who received PA 1 h before the start of surgery, every 3 h during surgery, and twice a day for 24–72 h after surgery. Conclusion: Operative outcomes after LS improved after the standardization of the operative procedure. The administration of PA 1 h before surgery and every 3 h during surgery seems to be sufficient to prevent surgical‐site infection during LS.